Application of artificial intelligence in additive manufacturing (3D printing) - Nevludov, I. Sh.; Sotnik, S. V. (ONUT Publishing House, 2025)
The paper presents a comprehensive analysis of artificial intelligence application to improve additive manufacturing quality. Systemic problems of modern 3D printing are identified: quality instability, high defect probability, and labor-intensive model preparation. Six key AI-based quality control methods are analyzed: digital twin, intelligent monitoring, predictive modeling, defect classification, predictive maintenance, and generative design. The combination of deep learning methods (CNN, U-Net, LSTM/GRU) with classical machine learning algorithms (XGBoost, Random Forest) and explainable AI technologies (XAI) ensures high defect detection accuracy and decision interpretability. Particular attention is given to the digital twin concept as an integrating platform for creating a dynamic virtual replica of the printing process. The results confirm that AI integration represents a fundamental transformation of approaches to design, production, and quality control in additive technologies.
Застосування штучного інтелекту у адитивному виробництві (3D-друк)
У роботі представлено комплексний аналіз застосування штучного інтелекту для підвищення якості адитивного виробництва. Визначено системні проблеми сучасного 3D-друку: нестабільність якості, висока ймовірність дефектів та трудомісткість підготовки моделей. Проаналізовано шість ключових методів контролю якості на основі ШІ: цифровий двійник, інтелектуальний моніторинг, прогностичне моделювання, класифікація дефектів, прогнозне обслуговування та генеративний дизайн. Поєднання методів глибокого навчання (CNN, U-Net, LSTM/GRU) із класичними алгоритмами машинного навчання (XGBoost, Random Forest) та технологіями пояснюваного ШІ (XAI) забезпечує високу точність виявлення дефектів та інтерпретованість рішень. Особливу увагу приділено концепції цифрового двійника як інтегруючої платформи для створення динамічної віртуальної копії процесу друку. Результати підтверджують, що інтеграція ШІ становить фундаментальну трансформацію підходів до проектування, виробництва та контролю якості в адитивних технологіях.
Keywords: Artificial intelligence; additive manufacturing; quality control; digital twin; intelligent monitoring; predictive modeling